Mutu Keju Putih Rendah Lemak Diproduksi Dengan Bahan Baku Susu Modifikasi - abubakar abubakar (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
This research was conducted to investigate the quality of low-fat white cheese produced using raw material of modified milk. Five treatments applied were (A1) Using reduced fat (60%) milk, (A2) Using emulsion of corn oil in skim milk (replacing milk fat with corn oil), (A3) Using emulsion of corn oil in skim milk and addition of whey protein concentrate (replacing milk fat with corn oil and the addition of whey protein concentrate=WPC), (A4) Using skim milk and water emulsion oil in water, and (A5) replacing milk fat with corn oil and the addition of probiotic (Lactobacillus casei). Each treatment was replicated three times. The selected that skim milk in corn oil emulsion with the addition of probiotics, the results showed had cheese quality characteristics as follow: yield 12.94±0.16%, hardnes 48.07±10.12 g, softness 8.51±0.54 kg/s, moisture content 50.37±1.60%, ash content 7.38±1.75% (dry matter), fat content 41.06±6.07% (dry matter), protein content 37.85±3.25% (dry matter), phosphorus content 346.62±25.61 mg/100g (dry matter), calcium content 860.78±87.91 mg/100g (dry matter), white color, regular texture, not flavorfull, salty taste, soft texture, elastic, ordinary preference acceptance.